Melodrama em falso e pedagogia social de Capitu, de Luiz Fernando Carvalho: a adaptação de Dom Casmurro para o audiovisual em três lições - Betella, Gabriela Kvacek [UNESP] (My University, 2014)
Some esthetical particularities of Luiz Fernando Carvalho’s micro-series reveal, in the nineteenth century Brazil, the capacity of the literary and audiovisual discourse to represent some singularities of the Brazilian social life from the past, as well as pointing to existential problems of the class representative that leads the plot, instigating reflections in the present. The treatment offered to the class struggle by the Machadian narrative and by the Rede Globo’s adaptation, just as the way in which the existential drama is expounded, disclose a kind of reception among readers/viewers which is capable of reviewing the historical past in times that ask for such a revision, even though the television series bets on the non-conventional. Machado presented the tension between representation and truth (as well as between emotion production and reflection) with the transfiguration of the tragic pathos and the mobilization of the patriarchal figure to the melodramatic bias. Although increased by the irony orchestrated by the scenic elements, in the audiovisual version such Machadian solutions would be apt to lose their strength to unmask the social subjects; on the other side, the intensification of the melodrama can make evident what Machado disguised with less obvious narrative intentions.

Particularidades estéticas da microssérie de Luiz Fernando Carvalho revelam no Brasil do século XXI a capacidade dos discursos literário e audiovisual de representar singularidades da vida social brasileira do passado, bem como apontam problemas existenciais do representante de classe que conduz o enredo, provocando reflexões no presente. O tratamento oferecido à luta de classes pela narrativa machadiana e pela adaptação da Rede Globo, assim como o modo através do qual o drama existencial é exposto, revelam um tipo de recepção entre leitores/espectadores, capazes de rever o passado histórico em tempos que pedem tal revisão, ainda que a série televisiva aposte forçosamente no anticonvencional. Machado apresentou a tensão entre representação e verdade (bem como entre produção de emoção e de reflexão) com a transfiguração do pathos de tragédia e a mobilização da figura patriarcal para o viés melodramático. Embora acrescidas de uma ironia orquestrada pelos elementos cênicos na versão audiovisual, tais soluções machadianas tenderiam a perder a força de desmascaramento dos sujeitos sociais, contudo a intensificação do melodrama pode evidenciar o que Machado disfarçou com intenções narrativas menos óbvias. Palavras-chave: Literatura e televisão; Machado de Assis; Dom Casmurro; Luiz Fernando Carvalho
Melodrama in false and Capitu´s social pedagogy by Luiz Fernando Carvalho: the adaptation of Dom Casmurro to the audiovisual in three lessons
Keywords: Literature and television; Machado de Assis; Dom Casmurro; Luiz Fernando Carvalho; Literatura e televisão; Machado de Assis; Dom Casmurro; Luiz Fernando Carvalho